The Effect of the Percentage of Non-Dairy Cream and Moringa Leaves Filtrate on the Chemical and Organoleptic Characteristics of Peanut Ice Cream - Antika, Silvy; Lubis, Linda Masniary; Sinaga, Hotnida (Talenta Publisher, 2023)
This research was conducted to determine the effect of the percentage of non-dairy cream and Moringa leaves filtrate on the characteristics of peanut ice cream. This research used a Completely Randomized Design (RAL) method with two factors i.e the percentage of non-dairy cream (10, 20%, 30%, and 40%) and the percentage of Moringa leaves filtrate (0%, 10%, 20%, and 30%) with three repetitions. The results showed that the percentage of non-dairy cream had a highly significant effect on fat and water content, total dissolved solids, overrun, melting time, and hedonic value of texture. The percentage of Moringa leaves filtrate had a highly significant effect on protein, fat, and water content vitamin C content, total dissolved solids, overrun, melting time, and hedonic value of taste. Interaction between the percentage of non-dairy cream and moringa leaves filtrate had a highly significant effect on fat content, total soluble solids, and overrun. Antioxidant analysis was conducted on the best treatment with a percentage of 40% non-dairy cream and 30% Moringa leaves filtrate with IC50 of 146.6368 ppm.